An Ocular Chameleon. (October 2022) - Shaffi, Mohamed; Saad, Nick; Arnold, Jennifer; Parker, Geoffrey; Nguyen, Daniel; Eftekhar, Behzad
Patients presenting with transient visual loss is common in emergency departments. Neurologists, ophthalmologists and emergency care physicians may be called upon to evaluate such patients. Monocular visual loss should be differentiated from the binocular involvement as the oetologies, investigations and management of such patients differ considerably. We report a case of monocular visual loss that involved predominantly one eye but affected the other side independently, albeit less frequently. A meticulous history, thorough general, neurological and ophthalmological examinations are necessary in such patients to identify the cause and to treat appropriately. Ocular ischemic syndrome (OIS) is due to chronic hypoperfusion of the structures supplied by ophthalmic artery leading to monocular visual loss. Stenosis of the ipsilateral internal carotid artery from a variety of causes is the main underlying mechanism. The first case of OIS was reported by Hedges in 1963 and the term was coined later by Barry and Magargal. Ocular ischemic syndrome is an important differential diagnosis to consider especially in older people and those with vascular risk factors. An overview of important differential diagnosis, clinical features and treatment of OIC are discussed in this article. A multidisciplinary team is optimal for the management of ocular ischemic syndrome.